FORAMINIFERI PLEISTOCENICI ED INTERPRETAZIONI PALEOAMBIENTALI IN UN AFFIORAMENTO DELLA SICILIA NORD-ORIENTALE (ROMETTA, MESSINA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The foraminiferal assemblages of clayey marls from Rometta (Messina, Sicily) are here quantitatively analyzed. The sediments are Early Pleistocene in age. The planktonic climatic curve shows that the deposition of marls occurred during intervals alternatively characterized by cold and warm water temperatures.Benthic assemblages testify a sedimentation depth of about —700 m, in the upper epibathyal zone. In order to evaluate the paleoenvironmental significance of benthic Foraminifera the following parameters were considered• Some benthic taxa seem to be quantitatively controlled by different paleoenvironmental factors: a) by grain size of sediments as Eponides turgidus, Gyroidinoides neosoldanii, G. laevigatus, frequent in clayey samples or as Trifarina angulosa, agglutinated forms, miliolids, common In sandy samples; b) by climatic changes as Bolivina pygmaea, abundant in cold Intervals or as Hoeglundina elegans more common in warm intervals.a) Faunal Density (B Foraminiferal Number), expressed by the number of benthic specimens per gram of sediment in each sample; b) Specific Diversity or Diversity Index, expressed by the number of specimens per number of species in each sample; c) Degree of Specialization, expressed by the total per centages of the five more abundant species in each sample.It seems possible to suggest an uplift rate of the area of 1 .4—1 .6 m/ 1000 y since the deposition of the Rometta marls.
Keywords: Foraminifera; Early Pleistocene; Sicilian; North—Eastern Sicily; Paleoecology; Climatic curves; Biostratigraphy.